2020
DOI: 10.1016/j.jsps.2020.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of sesamin on cardiovascular disease and its associated risk factors

Abstract: Sesamin, a major lignin isolated from sesame ( Sesamum indicum ) seeds and sesame oil, is known to possess antioxidant and anti-inflammatory properties. Several studies have revealed that oxidative stress and inflammation play a major role in a variety of cardiovascular diseases (CVDs). This comprehensive review summarizes the evidence on the effects of sesamin on CVD and its risk factors, principally due to its antioxidant properties. Specifically, this review highlights the mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 102 publications
(166 reference statements)
1
52
0
Order By: Relevance
“…Several in vitro and in vivo studies illustrate the neuroprotective role of sesamin against cerebral ischemia (Chung et al, 2010;Dar and Arumugam, 2013). Also, this major lignin compound has demonstrated other biological activities such as antihypertensive, atherosclerosis, thrombosis, antidiabetic, anticancer, cardiovascular, and antiinflammatory (Kumar et al, 2018;Dalibalta et al, 2020). Of note, sesamin has been previously shown to be effective against swine flu (influenza type A H1N1) through in silico and in vitro studies (Fanhchaksai et al, 2015).…”
Section: Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro and in vivo studies illustrate the neuroprotective role of sesamin against cerebral ischemia (Chung et al, 2010;Dar and Arumugam, 2013). Also, this major lignin compound has demonstrated other biological activities such as antihypertensive, atherosclerosis, thrombosis, antidiabetic, anticancer, cardiovascular, and antiinflammatory (Kumar et al, 2018;Dalibalta et al, 2020). Of note, sesamin has been previously shown to be effective against swine flu (influenza type A H1N1) through in silico and in vitro studies (Fanhchaksai et al, 2015).…”
Section: Compoundmentioning
confidence: 99%
“…Sesame (Sesamum indicum L.) is an herbaceous annual plant cultivated for its edible seed, oil, and flavorsome value, belonging to the order Tubiflorae, family Pedaliaceae with many common names including gingelly, til, and benne seed (Bhat et al, 2014;Pathak et al, 2019). This oil crop is regarded as "queen of oilseeds" because of its property of resistance to oxidation and rancidity (Dalibalta et al, 2020). Sesame is widely cultivated in the tropical parts of Africa and Asia, India being one of the major producers with Myanmar, China, and Sudan (Majdalawieh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [ 195 ] demonstrated that puerarin administration attenuates VC by inhibiting inflammation. Sesamin, a lignin extracted from sesame seeds and sesame oil, has shown benefits in CVD [ 196 ]. Animal models exposed to this agent showed enhanced inhibition of platelet-derived growth factor (PDGF)-induced VSMC proliferation [ 197 ], attenuated degradation of collagen and elastin fibers [ 198 ] and diminished VSMC proliferation and migration [ 88 ].…”
Section: Possible Therapeutic Strategiesmentioning
confidence: 99%
“…Sesamin is found to protect against diverse tissue injuries, including brain injury [10,57], liver injury [58][59][60][61][62], lung injury [63,64], and renal injury [7,65,66]. Sesamin is also found to have diverse biological effects in amelioration of inflammation [4,5,67,68], oxidation [4,5,67], and apoptosis [60,61,66,68]. These studies indicate that sesamin may play a potential role in ameliorating intestinal injury, especially intestinal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Sesamin (Figure 1), a natural lignin compound, is isolated from sesame seeds, and it possesses health beneficial effects, including anti-inflammatory, anticancer, antihypertensive, antithrombotic, antidiabetic, antiatherogenic, antiobesity, and lipolytic effects [4,5], and ameliorates intestinal, renal, cardiac, brain, and hepatic injury [6][7][8][9][10][11]. However, the key modulatory properties and characteristics of sesamin and related mechanisms in ameliorating intestinal I/R injury remain to be explored.…”
Section: Introductionmentioning
confidence: 99%